(untitled) (Acta Scientiarum. Health Sciences, 2017)
The aim of this study was to evaluate the indicators of osteogenesis, cytotoxicity and genotoxicity of an experimental beta tri-calcium phosphate (experimental Î²-TCP) compared with two other bone substitutes: bovine hydroxyapatite (HA) (Bio-Oss® - Geistlich) and beta tri-calcium phosphate (Î²-TCP - Bionnovation). The cell viability and genotoxicity were measured by MTT and MNT assay, respectively. The indicators of osteogenesis were analyzed by alkaline phosphatase activity, total protein content, and calcium deposition. The MTT and MNT assay showed that none of the tested materials was cytotoxic nor genotoxic. Concerning the indicators of osteogenesis, it was observed that cells in contact with all the materials were able to induce the osteogenesis and this process was influenced by the period of the cell culture in contact with bone substitutes. Based on the results of this study, it was concluded that this experimental Î²-TCP appears to be a promising material as a bone substitute.